The Influence of Brand Trust, Product Quality, and Price on the Purchase Decision of Make Over Cosmetics (Case Study of Students at the Faculty of Economics and Business, Malikussaleh University) - Rika Wulandari; Rahmaniar Rahmaniar; Mariyudi Mariyudi; Ikramuddin Ikramuddin (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the influence of brand trust, product quality, and price on the decision to purchase Make Over cosmetics among students of the Faculty of Economics and Business at Malikussaleh University. This study uses a quantitative method with purposive sampling and multiple linear regression analysis. The results of the study indicate that brand trust, product quality, and price have a positive and significant influence on purchasing decisions. The stronger the consumers' trust in the brand, the higher the perceived product quality, and the more aligned the price is with the value received by consumers, the greater the likelihood that consumers will make a purchase. This study contributes to the development of marketing strategies and the improvement of consumers' purchasing decisions regarding Make Over cosmetics.